War and peace journalism in the 2023 Israel–Gaza war: A comparative analysis of the headlines of five international news agencies - Claudia Kozman (15448586) (2025)
Focusing on the news headlines of five international news agencies—AP, QNA, Reuters, TASS, and Xinhua—in their coverage of the first 4 months of the Israel–Gaza war, this comparative content analysis examined their use of war vs. peace journalism, alongside issue-specific conflict framing. Results revealed all agencies, except QNA, relied on war journalism more than peace journalism, where “no labels” was the most common indicator. Among the war journalism indicators, the focus on the “here and now” and “visible effects” suggests a preference for episodic battle coverage, a finding supported by the results of the issue-specific frames, where prognostic and diagnostic frames, indicative of thematic coverage, were dwarfed by a propensity to focus on military conflict and responsibility. Still, diplomacy prevailed, highlighting the multi-party orientation of this war and the tendency of the headlines to emphasize international diplomatic efforts to bring peace and reconciliation. Other Information Published in: International Communication Gazette License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/17480485251397756